Effect of Photoreduction of Semiconducting Iron Mineral—Goethite on Microbial Community in the Marine Euphotic Zone - Liu, Jia; Ge, Xiao; Ding, Hongrui; Yang, Shanshan; Sun, Yuan; Li, Yanzhang; Ji, Xiang; Li, Yan; Lu, Anhuai (Frontiers in Microbiology, 2022)
Marine euphotic zone is the pivotal region for interplay of light-mineral-microorganism and elements cycle, in which semiconducting minerals exist widely and iron-bearing goethite is a typical and widespread one. In this work, we have conducted in-depth researches on the effect of ferrous (Fe(II)) ions dissolved by photoreduction of goethite on microbial community structure and diversity. The mineral phase, structure and morphology of synthesized goethite were characterized by Raman, XRD, EDS, ESEM and AFM. Photoelectrochemical measurements tested photoelectric response and redox activity of goethite, having proved its significant property of photoelectric response with 44.11% increment of the average photocurrent density relative to the dark current density. The photoreduction experiments of goethite were conducted under light condition in simulated seawater. It has suggested the photoreduction of goethite could occur and Fe(III) was reduced to Fe(II). The dissolved Fe(II) from the photoreduction of goethite under light condition was nearly 11 times than that group without light after a 10-day reaction. Furthermore, results of microbial community sequencing analysis indicated that dissolved Fe(II) could affect the structure and regulate the decrease of microbial community diversity. The emergence of dominant bacteria associated with iron oxidation and transport protein has suggested their obvious selectivity and adaptability in the environment with adding dissolved Fe(II). This work revealed the photoreduction process of semiconducting goethite was remarkable, giving rise to a non-negligible dissolved Fe(II) and its selective effect on the structure, diversity, as well as the function of microbial community. This light-induced interaction between minerals and microorganisms may also further regulate correlative metabolic pathways of carbon cycle in the marine euphotic zone.